The Influence of Peer Group Education on Adolescents' Knowledge of Early Marriage - Wahyunisngsih, Wahyunisngsih; Sri; Ernawati, Ernawati; Aisyah, Sitti; Sari Wardani, Ratih; Siokal, Brajakson (Jurnal Ilmiah Global Education, 2025)
Early marriage remains a public health issue with negative impacts on adolescents, particularly in terms of reproductive health, education, and social well-being. Preventing early marriage requires effective educational strategies tailored to the characteristics of adolescents. This study aims to analyze the effect of peer group education on increasing adolescents' knowledge about early marriage. A quasi-experimental design with a pre-test and post-test control group approach was used, conducted in Borongloe Subdistrict, Bontomarannu District, Gowa Regency. The sample consisted of 100 adolescents aged 15–18 years, divided equally into intervention and control groups, with 50 participants each. The intervention was carried out through peer group discussions facilitated by trained peer educators, covering materials on reproductive health and the impacts of early marriage. Data were collected using standardized questionnaires and analyzed using the Wilcoxon and Mann-Whitney tests. The results showed a significant increase in knowledge in the intervention group compared to the control group. These findings indicate that peer group education is an effective and inclusive method that can enhance adolescents' understanding of the risks of early marriage. Peer group education is recommended as an intervention strategy in child marriage prevention programs, especially in areas with strong social norms.